Peningkatan Kemampuan Motorik Kasar Anak Usia 4-5 Tahun melalui Permainan Sirkuit Palola di KB Ar-Rohmah I Singosari - Sulaipah; Cicilia Ika Rahayu Nita; Siti Muntomimah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The aim of this research is to improve the gross motor skills of children aged 4–5 years through the application of the Palola circuit game at KB Ar-Rohmah I Singosari. Specifically, this study was directed to determine the process of implementing Palola circuit games as well as improving children's gross motor skills which include balance, agility, movement coordination and physical strength. This research method uses the Class Action Research (PTK) approach which is carried out in two cycles. Each cycle consists of four stages, namely planning, implementing actions, observation and reflection. The research subject was a 4–5 year old child at KB Ar-Rohmah I Singosari. Data collection techniques are carried out through observation, documentation and assessment sheets for children's gross motor abilities. Data analysis used qualitative and quantitative descriptive techniques by comparing the results of children's gross motor ability in pre-cycle, cycle I and cycle II. The research results show that the application of the Palola circuit game can improve the gross motor skills of children aged 4–5 years. This is shown by an increase in the percentage of children's gross motor skills achieved in each cycle. In pre-cycle, children's gross motor skills are in the low category. After taking action in cycle I, the child's gross motor skills have improved and are in the sufficient category. Furthermore, in cycle II there was a significant increase until it reached the good category. Thus, the Palola circuit game proved effective in improving the gross motor skills of 4–5 year old children at KB Ar-Rohmah I Singosari.